Oxidative stability of a heme iron-fortified bakery product: Effectiveness of ascorbyl palmitate and co-spray-drying of heme iron with calcium caseinate. (1st April 2016) - Alemán, Mercedes; Bou, Ricard; Tres, Alba; Polo, Javier; Codony, Rafael; Guardiola, Francesc
Highlights: Fortification with heme iron was studied in chocolate sandwich-type cookies. Antioxidant addition and heme iron encapsulation were used to minimize oxidation. Tocopherol loss and oxidation are reduced by ascorbyl palmitate (AP) addition. After 1 year of storage, control and Fe-encapsulated cookies are equally accepted. AP plus encapsulation is best at limiting oxidation and maintaining acceptability. Abstract: Fortification of food products with iron is a common strategy to prevent or overcome iron deficiency. However, any form of iron is a pro-oxidant and its addition will cause off-flavours and reduce a product's shelf life. A highly bioavailable heme iron ingredient was selected to fortify a chocolate cream used to fill sandwich-type cookies. Two different strategies were assessed for avoiding the heme iron catalytic effect on lipid oxidation: ascorbyl palmitate addition and co-spray-drying of heme iron with calcium caseinate. Oxidation development and sensory acceptability were monitored in the cookies over one-year of storage at room temperature in the dark. The addition of ascorbyl palmitate provided protection against oxidation and loss of tocopherols and tocotrienols during the preparation of cookies. In general, ascorbyl palmitate, either alone or in combination with the co-spray-dried heme iron, prevented primary oxidation and hexanal formation during storage. The combination of both strategies resulted in cookies that were acceptable from a sensory point of view after 1 year of storage.